Religion, violence, and peacebuilding realities, perspectives, and prospects = Religions, violence et construction de la paix : contextes, regards et perspectives - Religion, Violence, and Peacebuilding: Realities, Perspectives, and Prospects 2018 Löwen; Louvain-la-Neuve; Du Val d'Éprémesnil, Diane (Leuven Peeters Publishers & Booksellers, 2021)
This book is the outcome of a major conference held by 'Omnes Gentes' on the thematic religion, violence, and peacebuilding, celebrating the 100 years of the publication of 'Quod Iam Diu', the Encyclical of Pope Benedict XV 'On the Future Peace Conference' issued on 1st December, 1918. Authors from all continents have provided articles from their field of research and their context to illustrate the importance of religious insights and actions to promote peace in difficult times. Academics, ecclesiastical leaders, pastoral workers, and researchers from around the world, who are involved directly in the work of peacebuilding, shed light on specific contexts, historical perspective and actions, as well as inspiring prospects for the future. 'Omnes Gentes' is a collaboration of the Faculties of Theology of KU Leuven and UCLouvain, 'Lumen Vitae', and Missio-Belgium
Description based on publisher supplied metadata and other sources
7 English, 5 French contributions
Keywords: Peace-building -- Religious aspects -- Congresses; Violence -- Religious aspects -- Congresses; Electronic books; Peace-building - Religious aspects; Violence - Religious aspects; Conference papers and proceedings; Konferenzschrift